Systemic adverse drug events to topical prostaglandin analogs for treating glaucoma: a retrospective focused pharmacovigilance study - Kannan Sridharan (BMC Ophthalmology)
Abstract Background Prostaglandin analogs are first-line treatments for open-angle glaucoma due to their proven efficacy in reducing intraocular pressure. Despite their topical administration, systemic adverse drug Events (ADEs) have been reported. This study investigates the systemic ADEs associated with topical prostaglandin analogs using the United States Food and Drug Administration (USFDA) Adverse Drug Event Reporting System (AERS) database. Methods The USFDA AERS database was queried for reports on prostaglandin analogs from March 2004 to March 2024 in this retrospective pharmacovigilance study. Data were deduplicated and analyzed using disproportionality analysis with both frequentist and Bayesian approaches. Reports on systemic ADEs where topical prostaglandin analogs were the primary suspect were included. Statistical analysis was performed using descriptive statistics and the chi-square test for categorical variables. Results A total of 30,853 reports were analyzed, predominantly involving latanoprost and bimatoprost, with most patients being elderly and female. In general, hypersensitivity reactions were the most common systemic adverse events reported with prostaglandin analogs. Varied systemic adverse events were observed within the class as latanoprost was linked to conditions like angina pectoris, atrial tachycardia and Meniere’s disease, bimatoprost to lentigo maligna melanoma, and tafluprost to labyrinthitis and skin discoloration. Notably, tafluprost had a significantly higher occurrence of death compared to other prostaglandin analogs, yet the causal relationship has not been established for this association due to unavailability of critical data on temporality and potential confounders including concomitant diseases/drugs and severity of the disease. Conclusion Prostaglandin analogs are associated with systemic ADEs, particularly in elderly and female patients. The most reported systemic adverse event was hypersensitivity reactions for the class and cardiac events for latanoprost. Tafluprost was observed with higher mortality statistically, yet causal relationship could not be established in the absence of details on the potential confounders. The findings emphasize the need for continuous monitoring of adverse reactions, and consideration of patient-specific factors when prescribing these medications.